Symptoms, medical course and procedures in foetal alcohol syndrome - Horecka-Lewitowicz, Agata; Lewitowicz, Piotr; Adamczyk-Gruszka, Olga; Skawiński, Dariusz; Szpringer, Monika (Medical Studies/Studia Medyczne, 2013)
The effects of alcohol consumption by a pregnant woman are irreversible. Developing organs are damaged in children subject to prenatal alcohol exposure; the central nervous system is the most exposed to the toxic effects of alcohol. The type and extent of the damage in the foetus depends, among others, on the amount of consumed alcohol, the time span during which it is consumed, the stage of development of the foetus, as well as the state of health and the degree of nutrition of the pregnant woman. Characteristic symptoms, which are results of the teratogenic effects of alcohol in foetal life, can be observed in subsequent phases of the child’s development. Apart from the somatic changes (especially the characteristic facial appearance and short stature), one may observe disorders in functioning at school, among peers and in the family. Early diagnosis (until the age of 6), the environment in which the child develops, undertaking a therapy adjusted to the capabilities of the patient and the family, adjusting requirements at school and including the whole family in the therapy are significant factors which influence further functioning of the child.